Conspiracy theories, clinical decision-making, and need for bioethics debate: A response to Stout - Varelius Jukka (Wiley, 2025)
Although people who endorse conspiracy theories related to medicine often have negative attitudes toward particular health care measures and may even shun the healthcare system in general, conspiracy theories have received rather meager attention in bioethics literature. Consequently, and given that conspiracy theorizing appears rather prevalent, it has been maintained that there is significant need for bioethics debate over how to deal with conspiracy theories. While the proposals have typically focused on the effects that unwarranted conspiracy theories have in the public health context, Nathan Stout's recent argument concentrates on the impacts that such theories have at the individual level of clinical decision-making. In this article, I maintain that duly acknowledging the impacts of conspiracy theories that raise Stout's concern does not require bioethics debate over the proper response to the influence of conspiracy theories in healthcare. Having evaluated two possible objections, I conclude by briefly clarifying the purported import of the response to Stout.